Break with tradition - Nathan, Leslie Ann; The Center for Humanities ([Wisconsin : The Center for Humanities, 1986)
The break with tradition introduces students to the origins of modern art. Explains one of the most revolutionary aspects of impressionists painting, its use of color, as seen in the works of Monet, Pissarro and Renoir
Title from title screen
The Center for Humanities seminars in modern art
DVD format
Keywords: Post-impressionism (Art); Art, Modern -- History; Painting -- 20th century